Morphological Study on Development of Vascular Endothelium in Chick Embryo - Yaiko ​ Hara (Journal of Multidisciplinary Dental Research)
The vascular endothelium and hematopoietic stem cells are believed to derive from common progenitor cells called hemangioblasts. However, morphological study on the development of vascular endothelial cell has been scarce. The present study is intended to provide more morphological explanation of the differentiation process of the hemangioblast. We performed histological observation, using 10 four-day-old chick embryos. After fixation with 4% concentration paraformaldehyde, hematoxylin eosin staining, toluidine blue staining and immunostaining were performed in that order for observation of morphological changes of the detected cells. Blood corpuscles were aggregated in the dorsal aorta and the heart (that had been observed to beat in its preparation). Some red blood cells showed immunoreactivity to both anti-Flk-1(VEGFR2) and anti-CD31 antibody. Additionally, some blood cells had small vacuoles in the cytoplasm, and they fused to form one larger vacuole ultimately a balloon-like shape that was connected to endothelial cells. These cells were present in close proximity to the vascular endothelium. We reveal that some of the early embryonic blood cells differentiate into vascular endothelial cells. Keywords: Vasculogenesis, Angiogenesis, Hemangioblasts, Vascular endothelial cells